Opportune detections of global P-wave propagation from microseisms interferometry - Boué, Pierre; Tomasetto, Lisa (Comptes Rendus. Géoscience, 2023)
Global seismological observations are sensitive to oceanic forcings, namely microseisms. In addition to dominant surface waves, these sources generate body waves that travel through the deep structures of our planet. Despite these sources’ inherent complexity, interferometric methods allow isolating coherent waves for imaging applications. For a given station pair, only specific microseism events contribute to the illumination of a specific target. We propose an opportune workflow based on ocean sea state models to extract robust interferences. This approach is illustrated with a strong microseism source in the North Atlantic Ocean, occurring around December 9, 2014.